2005
DOI: 10.1038/labinvest.3700247
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of adenoviral gene transfer of bone morphogenic protein-7 on a corneal alkali injury model in mice

Abstract: An alkali burn in the cornea is a common serious clinical problem often leading to permanent visual impairment. Since transforming growth factor-b (TGF-b) is involved in the response to corneal injury, we evaluated the therapeutic effects of adenoviral gene transfer of mouse bone morphogenic proten-7 (BMP-7), which has antagonistic effects on TGF-b in tissue fibrosis. Burned cornea did not express endogenous BMP-7 mRNA and protein. Resurfacing of the burned cornea by invading conjunctival epithelium was accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 58 publications
3
39
1
Order By: Relevance
“…On the other hand, the reduction of TGF-␤, a profibrogenic stimulus for myofibroblast differentiation, in Vim Ϫ/Ϫ mice and in WFA-treated Vim ϩ/ϩ mice points to a suppression of a fibrotic switch elicited in genetic and pharmacological deficiency of vimentin. That direct blockade of TGF-␤ (39) or antagonizing its signaling mechanism in corneal cells (77) inhibits ␣-SMA expression in corneal stroma and restores corneal clarity in alkali injured mice further supports the idea that this cytokine is relevant to therapeutic strategies being considered for treatment of corneal fibrotic disorders (37). In this respect, the regulatory control of TGF-␤ biogenesis and its activity is associated with mechanical forces exerted by stromal myofibroblasts on the extracellular matrix that facilitates a positive feedback loop, where mechanical tension in the stroma promotes and sustains the myofibroblast phenotype through activation of ␣-SMA expression (78).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the reduction of TGF-␤, a profibrogenic stimulus for myofibroblast differentiation, in Vim Ϫ/Ϫ mice and in WFA-treated Vim ϩ/ϩ mice points to a suppression of a fibrotic switch elicited in genetic and pharmacological deficiency of vimentin. That direct blockade of TGF-␤ (39) or antagonizing its signaling mechanism in corneal cells (77) inhibits ␣-SMA expression in corneal stroma and restores corneal clarity in alkali injured mice further supports the idea that this cytokine is relevant to therapeutic strategies being considered for treatment of corneal fibrotic disorders (37). In this respect, the regulatory control of TGF-␤ biogenesis and its activity is associated with mechanical forces exerted by stromal myofibroblasts on the extracellular matrix that facilitates a positive feedback loop, where mechanical tension in the stroma promotes and sustains the myofibroblast phenotype through activation of ␣-SMA expression (78).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that gene introduction of BMP-7 also has a therapeutic effect on an alkali burn in mice, although its efficacy is less than that of Smad7. 109 Unlike in an alkali-burned cornea, Stevens-Johnson's syndrome is an inflammatory ocular surface disease caused by an autoimmune mechanism. Nevertheless, the main component of the disease consists of inflammation and scarring that are similar to those seen in a burned eye.…”
Section: Gene Therapy For the Treatment Of Corneal Inflammation And Fmentioning
confidence: 99%
“…16 Real-time RT-PCR for mRNAs of mouse TGF␤1, monocyte/macrophage-chemoattractant protein-1 (MCP-1), vascular endothelial growth factor (VEGF), and collagen I␣2 was performed at weeks 1, 2, and 4 using primers and probes shown in Table 1 as previously reported.…”
Section: Detection Of Mrnas Of Tnf␣ Tgf␤1 Mcp-1 and Vegf In Burnedmentioning
confidence: 99%
“…16,17 Ofloxacin ointment was topically administered twice a week in the first 2 weeks and then once a week until week 8 to reduce the risk of bacterial contamination. The eyes with obvious bacterial infection were excluded from the study.…”
Section: Alkali Burn In Mouse Eyesmentioning
confidence: 99%
See 1 more Smart Citation